2020
DOI: 10.1101/2020.01.07.897694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local retinoic acid directs emergence of the extraocular muscle functional unit

Abstract: Coordinated development of muscles, tendons, and their attachment sites ensures emergence of functional musculoskeletal units that are adapted to diverse anatomical demands among different species. How these different tissues are patterned and functionally assembled during embryogenesis is poorly understood. Here, we investigated the morphogenesis of extraocular muscles (EOMs), an evolutionary conserved cranial muscle group that is crucial for the coordinated movement of the eyeballs and for visual acuity. By … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…The fact that muscle did not attach randomly to nearby bone but changed its morphology toward the distal tendon tissue implied a hypothesis that diffusible molecule(s) secreted from tendon cells could attract myofibers. Indeed, recent studies reported the involvement of retinoic acid in the formation of the extraocular functional unit (Comai et al, 2020), and FGF or BMP signaling were active at the interface of the embryonic tendon and muscle (Eloy-Trinquet, Wang, Edom-Vovard, & Duprez, 2009; Wang et al, 2010). However, cell adhesion molecule (Hasson et al, 2010) or ECM (Kutchuk et al, 2015) can also play parallel roles.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that muscle did not attach randomly to nearby bone but changed its morphology toward the distal tendon tissue implied a hypothesis that diffusible molecule(s) secreted from tendon cells could attract myofibers. Indeed, recent studies reported the involvement of retinoic acid in the formation of the extraocular functional unit (Comai et al, 2020), and FGF or BMP signaling were active at the interface of the embryonic tendon and muscle (Eloy-Trinquet, Wang, Edom-Vovard, & Duprez, 2009; Wang et al, 2010). However, cell adhesion molecule (Hasson et al, 2010) or ECM (Kutchuk et al, 2015) can also play parallel roles.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the ear, tendons that connect six extraocular muscles to the eye are essential for normal eye movement and defects in these tendons have been linked to ocular movement disorders including Brown syndrome and congenital fibrosis of the extraocular muscles (CFEOM), 100,101 where a shortened superior oblique tendon contributes to limited movement and passive elevation of the eye. While more is known about mechanisms governing the development of extraocular muscles, 102,103 there is a paucity of research on ocular tendon development. Ocular tendons have been identified in developing mice and zebrafish and the initiation of their formation during development is muscle independent, similar to their limb counterparts 47,104 .…”
Section: Tendon Developmental Disorders In Craniofacial Sensory Organsmentioning
confidence: 99%